Studies on Thin-shells and Thin-shell Wormholes - Övgün, Ali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The study of traversable wormholes is very hot topic for the past 30 years. One of the best possible way to make traversable wormhole is using the thin-shells to cut and paste two spacetime which has tunnel from one region of space-time to another, through which a traveler might freely pass in wormhole throat. These geometries need an exotic matter which involves a stress-energy tensor that violates the null energy condition. However, this method can be used to minimize the amount of the exotic matter. The goal of this thesis study is to study on thin-shell and thin-shell wormholes in general relativity in 2+1 and 3+1 dimensions. We also investigate the stability of such objects. Keywords: Wormhole, Thin-Shells, Junction Conditions, Black Holes.

OZ: Solucan delikleri bilim ve bilim kurgu dunyasının en populer konularından biridir. 30 sene boyunca populeritesini daha da artırdı. Olası solucan deligi yapabilmek icin en kullanıslı ve kararlı yontemlerden biri Einsteinin yercekimi kuramı icerisinde ince kabuklu uzay solucan deligi yapmaktır. Bu kuramlarda ¨onemli olanı gecisi yapacak olanın, solucan deliginin bogazından serbestce gecisine olanak vermesi ve belirli sartları sa˘glamasıdır, ve egzotik madde miktarını en d¨us¸ ¨uk seviyeye c¸ekebilmektir. Bu c¸alıs¸mada kara deliklerin etrafında olus¸abilecek ince-kabuklu zarı, ve bunları kullanarak kararlı yapıda solucan deli˘gi olus¸turmaya c¸alıs¸tık. Anahtar Kelimeler: Solucan Delikleri, Kara Delikler,
Doctor of Philosophy in Physics. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2016. Co-Supervisor: Assoc. Prof. Dr. S. Habib Mazharimousavi, Supervisor: Prof. Dr. Mustafa Halilsoy.
Keywords: Physics; Gravitational Physics; General Relativity; Traversable Wormholes; Wormhole; Thin-Shells; Junction Conditions; Black Holes; Thin - shell and thin - shell wormholes